Three theoretical approaches to L2/FL teaching put into practice - Beltramino, Florencia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Applied Linguistics -AL- has been gathering momentum since its origins in the 1950’s and ever since has been contributing with practical solutions to second language -L2- and foreign language -FL- teaching and learning with such a prolific body of knowledge that is an intellectual feat to keep up to date with it. From AL corpus three theoretical models were selected: Innatist, Sociolinguistic and Neurolinguistic as a proposal for addressing language teaching based on AL theoretical underpinnings. Departing from the chosen methods, simple and easy-to-apply classroom practices are suggested and explained. They are meant for classroom settings conformed by adolescents and young adults whose L2/FL language is beginners or false beginners and whose objective is that of learning English for general purposes.